Impact Of Varicella Vaccination On The Incident Of Varicella - Erza Anugrah; Nurelly N Waspodo; Adharia, Adharia (Sean Institute, 2024)
Varicella is an infectious disease caused by the varicella-zoster virus (VVZ). This viral infection affects the mucosa and skin. Varicella virus is spread mainly through the respiratory route and less commonly through direct contact with the lesions. Diagnosis of varicella can be made clinically through careful history taking and physical examination. WHO recommends general vaccination in places where chickenpox is still a public health problem. In Indonesia, varicella vaccine is still an optional immunisation group, not yet a mandatory immunisation programme by the government. . In some cases, people who have had the varicella vaccine may experience chickenpox again after direct contact with a person with chickenpox or direct infection with the varicella-zoster virus. However, people who have had the varicella vaccine tend to experience milder symptoms than people who have not had the vaccine. .